GOOD CORPORATE GOVERNANCE MECHANISM AND POLITICAL CONNECTION TOWARDS CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE - Herlina - Lusmeida; Karin Zaneta Halim (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2022)
This study aims to examine the effect of good corporate governance mechanisms by using the proportion of independent commissioners and board commissioner sizes and to examine the effect of political connection on corporate social responsibility disclosure using the GRI standard. The research population is 100 compass companies listed on the Indonesia Stock Exchange in 2018-2020. samples were selected using a purposive sampling method and obtained 267 samples. The analytical tool used is multiple regression. Based on the results of this study, the board commissioner size and political connection have a positive effect on CSR disclosure, while the independent board of commissioners found no evidence that the independent board of commissioners had a positive effect on CSR disclosure. This study contributes to the political connection, corporate governance mechanism, and CSR disclosure by identifying CSR disclosures based on the GRI standard to the most detailed level, which is 250 disclosure indicator items. Meanwhile, previous research only identifies CSR disclosure up to 77 GRI indicators without paying attention to the sub-indicators in detail.